Q: What is the equation of 1 7 and -2 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Points: (1, 3) and (-2, 1) Slope: 2/3 Equation: y = 2/3x+7/3 or as 3y = 2x+7

im assuming your equation is 2x + 1 = 7 in this case you need to find what x equals 2x + 1 = 7 2x + 1 - 1 = 7-1 2x = 6 x = 3 put it back into the equation to check if your answer is correct 2(3) + 1 = 7 6 + 1 = 7 7 = 7 Correct! if your equation is 2x - 1 = 7 x = 4 check it 2(4) - 1 = 7 8 - 1 = 7 7 = 7 Correct! if your equation is 2x1 = 7 x = 7/2 check it 2(7/2)1 = 7 2(7/2) = 7 2 * 7 / 2 = 7 14/2 = 7 7 = 7 Correct! hope i got your equation right. if not you can message me on my message board to get more help.

3x-1 = 7 3x = 8X= 8/3 = 2+2/3

Assuming the two points are (-4,-7) and (3,2) the equation for the slope would be (3-(-4))/(2-(-7)) which equals 7/9. If we use y=mx+b and the point (3,2) you get 2=(7/9)*3+b which simplifies to 2=2 1/3+b then by subtracting 2 1/3 from both sides you are left with b= -1/3. Thus the equation is y=7/9x-1/3.

x - 2 5/7 = 2/3 x - 19/7 = 2/3 x = 2/3 - 19/7 = 14/21 - 57-21 = -43/7 = -6 and 1/7

Related questions

Points: (1, 3) and (-2, 1) Slope: 2/3 Equation: y = 2/3x+7/3 or as 3y = 2x+7

im assuming your equation is 2x + 1 = 7 in this case you need to find what x equals 2x + 1 = 7 2x + 1 - 1 = 7-1 2x = 6 x = 3 put it back into the equation to check if your answer is correct 2(3) + 1 = 7 6 + 1 = 7 7 = 7 Correct! if your equation is 2x - 1 = 7 x = 4 check it 2(4) - 1 = 7 8 - 1 = 7 7 = 7 Correct! if your equation is 2x1 = 7 x = 7/2 check it 2(7/2)1 = 7 2(7/2) = 7 2 * 7 / 2 = 7 14/2 = 7 7 = 7 Correct! hope i got your equation right. if not you can message me on my message board to get more help.

Points: (1, 3) and (3, 7) Slope: 2 Equation: y = 2x+1

Points: (1, 4) and (2, 7) Slope: 3 Equation: y = 3x+1

2n - 7 = - 1 add 7 to each side 2n - 7 + 7 = - 1 + 7 2n = 6 divide each sides integer by 2 (2/2)n = 6/2 n = 3 ---------------check in original equation 2(3) - 7 = - 1 6 - 7 = - 1 - 1 = - 1 ----------------checks and equation is satisfied

Points: (1, 5) and (2, 7) Slope: 2 Equation: y = 2x+3

Points: (-1, 7) and (-2, 3) Slope: 4 Equation: y = 4x+11

2+ (2-3) / 7(3+9) 2+(-1)/7(12) = 1/84 or .012 if you meant to multiply the WHOLE equation by 7 it would be: 7[2+(2-3)/(3+9)] 7[2+(-1)/(12)] 7(1/12)= 7/12 or .583

3x-1 = 7 3x = 8X= 8/3 = 2+2/3

Assuming the two points are (-4,-7) and (3,2) the equation for the slope would be (3-(-4))/(2-(-7)) which equals 7/9. If we use y=mx+b and the point (3,2) you get 2=(7/9)*3+b which simplifies to 2=2 1/3+b then by subtracting 2 1/3 from both sides you are left with b= -1/3. Thus the equation is y=7/9x-1/3.

x - 2 5/7 = 2/3 x - 19/7 = 2/3 x = 2/3 - 19/7 = 14/21 - 57-21 = -43/7 = -6 and 1/7

Points: (2, 5) and (4, 3) Slope: -1 Equation: y = -x+7